Simulation of oil palm root water uptake by using 2D numerical soil-water flow model - Lisma Safitri; Andiko Putro Suryotomo; Satyanto Krido Saptomo (PERTETA, 2021)
The sustainability in oil palm plantation requires a specific information about the oil palm root water uptake. As an introduction, it is find of interest to simulate the root water uptake and water content pattern of oil palm. The study was performed by applying the 2D simulation soil-water flow model to 17th year old oil palm tree located in Siak, Riau with the loam soil type. The climate data during 22 Nov – 22 Dec 2018 was used to predict the evapotranspiration. The simulation over 30 days based on Richard equation illustrated the root water uptake distribution, water content change, pressure head and flow velocity. The most intensive root water uptake occurred in the upper root zone of oil palm tree as an impact of the higher root density. The significant root water uptake in the upper root zone lead to the decreasing of water content and increasing of pressure head. Consequently, there was a change of water flow direction from the wet area in the downward and sideward do dry root zone as the water supply to the oil palm tree. The validation test showed that the simulation performed well (R2 = 0.724 and RMSE = 0.0066).